2016
DOI: 10.17559/tv-20150328135652
|View full text |Cite
|
Sign up to set email alerts
|

Fault diagnostics of acoustic signals of loaded synchronous motor using SMOFS-25-EXPANDED and selected classifiers

Abstract: Original scientific paper A system of fault diagnostics of loaded synchronous motor was proposed. Proposed system was based on acoustic signals of loaded synchronous motor. A new method of feature extraction SMOFS-25-EXPANDED (shorted method of frequencies selection-25-Expanded) was proposed. Presented method was analysed for 3 classifiers: LDA (Linear Discriminant Analysis), NN (Nearest Neighbour), SOM (Self-organizing Map). Analysis was carried out for real incipient states of loaded synchronous motor. Acous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Then, especially in vibroacoustic diagnostics (WA), it is possible to determine changes in the WA signal resulting from a change in the technical condition of the tested object. There are many publications in the literature presenting the use of vibroacoustic diagnostics (in some cases in combination with thermal imaging diagnostics) in automotive, railroad or air vehicles [19,[29][30][31][32][33][34][35][36]. Based on the changes presented in Figure 6, it can be concluded that the wear of the friction material affects the increase in the amplitude of vibration acceleration from the holder with friction linings.…”
Section: Resultsmentioning
confidence: 99%
“…Then, especially in vibroacoustic diagnostics (WA), it is possible to determine changes in the WA signal resulting from a change in the technical condition of the tested object. There are many publications in the literature presenting the use of vibroacoustic diagnostics (in some cases in combination with thermal imaging diagnostics) in automotive, railroad or air vehicles [19,[29][30][31][32][33][34][35][36]. Based on the changes presented in Figure 6, it can be concluded that the wear of the friction material affects the increase in the amplitude of vibration acceleration from the holder with friction linings.…”
Section: Resultsmentioning
confidence: 99%
“…With the increasing size and complexity of data, neuroevolution is used to optimize the strengths of neural connections and the structure of the network, such as conventional neuro evolution (CNE) [17] and differential evolution for neural networks (DENN) [18]. Moreover, some scholars have combined neural networks with data feature extraction technology to improve the fault recognition ability [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Reference [29] carries out recognition of armature current of DC generator with the FFT, Method of Selection of Amplitudes of Frequencies and Linear Discriminant Analysis. Reference [30] proposes a new method of feature extraction SMOFS-25-EXPANDED (shorted method of frequencies selection- to analyze the acoustic signals for real incipient states of loaded synchronous motor.…”
Section: Introductionmentioning
confidence: 99%